Perceptions of minimum age at marriage laws and their enforcement: qualitative evidence from Malawi - Andrea J. Melnikas; Nancy Mulauzi; James Mkandawire; Sajeda Amin (BMC, 2021)
Abstract Background Child marriage in Malawi is a significant problem with 42.1% of women 20-24 married by age 18. In 2017 the Malawi government formalized legislation to make marriage under age 18 illegal; violators are subject to fines. While leveraging laws to reduce child marriage is common, the enactment of laws and their enforcement has led to some novel practices. One such practice observed in Malawi is marriage withdrawal, where the community intervenes when a child marriage has taken place to force the girl to return to her natal home. Methods This paper is a qualitative analysis of perceptions regarding marriage withdrawal. We conducted focus group discussions and in-depth interviews with married and unmarried adolescents, parents of adolescents, and key community members in Mangochi and Nkhata Bay. Data were collected as part of an evaluation of the More Than Brides Alliance program aimed at delaying marriage and improving access to sexual and reproductive health services in Malawi. Results The knowledge that violation of marriage laws entails substantial fines is widespread and marriage withdrawals are seen by some respondents as a way of enforcing the spirit of child marriage laws while avoiding fines. Some respondents suggest that enforcement of marriage laws has an unintended effect of driving marriages underground. One important disconnect between the laws and the realities of child marriage practices in these communities is that the law holds parents responsible for the marriage and for preventing it, while parents do not necessarily exercise control, particularly when the marriage is precipitated by pregnancy. While parents and other adults view withdrawals as an acceptable resolution of a problematic child marriage, girls noted many drawbacks for withdrawn girls such as stigma and limited education and livelihood opportunities once withdrawn. Conclusions Our exploration of perceptions about marriage laws suggest that the imposition of fines may have some unintended consequences, both driving the practice underground and encouraging practices to evade fines, and may be associated with unintended consequences for adolescent girls. Programs to address child marriage should include other approaches that address more distal drivers including poverty and lack of alternatives to child marriage. Trial registration This work is part of an RCT registered August 4, 2016 in the AEA RCT registry identified as: AEARCTR-0001463 . See: https://www.socialscienceregistry.org/trials/1463